Succession Planning Effectiveness: A Case Study of UKM - Fatimah, Othman (2012)
This quantitative research aimed to determine the effectiveness of succession planning based on the perception of administrative officers (N Scheme) in UKM. Further, the survey research using systematic sampling aimed to examine the relationship and influence of career development, knowledge management practices, and leadership styles (autocratic and democratic) on the effectiveness of the succession planning. The finding shows the majority of the respondents perceived that the succession planning, which has been implemented by UKM, is highly effective. In addition, the respondents also strongly agreed with the activities of knowledge acquisition, knowledge creation and knowledge transfer which have been practicing in UKM, whereas knowledge storage, knowledge sharing, and career developement were perceived moderately by the respondents. The finding also reveals that there is no significant difference between male and female in their perception towards succession planning effectiveness. Besides, there is also no significant difference among the officers Grade N41 to N54 on their perception on the effectiveness of career development and knowledge management practices. Essentially, all predictors of the in this study have no significant correlation with the effectiveness of succession planning. This indicated that there was no significant relationship between the predictors and succession planning effectiveness. In other words, there are other additional predictors that are important in explaining the effectiveness of succession planning h have not been considered in this study. Implications of the findings, suggestions for future studies and recommendations for proactive actions to be taken by Human Resources Division of UKM were also presented.